Assessing risk and financial strength of general insurers in Malaysia - Saiful Hafizah Jaaman,; Noriszura Ismail,; Noriza Majid, (Penerbit ukm, 2007)

(untitled)
Risk creates an economic burden for society by compelling the creation of reserve funds, raising the cost of certain services and excluding the provision of some goods and services. Because of the threat of failure and insolvency, the risk of insurance company is closely monitored by managers and regulators. Ever since the 1997 financial crisis that lead to the liberalisation in the insurance industry, monitoring insurers that are in or heading a hazardous condition has created a challenge to the regulatory bodies. Failure on the part of an insurer to give due performance of its obligations can lead to the policyholders losing part of the premiums paid or worse they or the third party may be deprived of any compensation due when claims are made. Capital, also called surplus or equity, is the excess of assets over liabilities. Technical insolvency occurs when obligations exceed assets requiring intervention by the regulators. Solvency of an insurer is intimately linked to the condition of its financial statement. Risk-based capital (RBC) is the theoretical amount of capital needed to absorb the risks of conducting a business. For insurance, it is the amount of capital necessary to assure major parties to insurer insolvency that the danger of failure is acceptably low. Generally, RBC categorises risk into different components to cover the liquidity, asset management and leverage aspects of an insurer. In this study, the risk-based capital is attempted to assess the risk and financial strength of twenty general insurers in Malaysia from the years 2002 to 2004. Our study found that based on RBC about a fifth of the insurers need regulatory intervention